An exploratory proton MRS examination of gamma-aminobutyric acid, glutamate, and glutamine and their relationship to affective aspects of chronic pain. (February 2021) - Legarreta, Margaret D.; Sheth, Chandni; Prescot, Andrew P.; Renshaw, Perry F.; McGlade, Erin C.; Yurgelun-Todd, Deborah A.
Highlights: Pain catastrophizing was associated with a reduction in GABA/Cre in the MPFC. Pain intensity was negatively correlated with GABA/Cre. No significant relationships found between Glu/Cre or Gln/Cre and pain measures. Abstract: Veterans experience chronic pain more frequently than civilians. Identification of neurobiological mechanisms underlying the pathophysiology of chronic pain in a veteran population may aid in the development of novel treatment targets. In this pilot proof-of-concept study, veterans with chronic pain (N = 61) and no chronic pain (N = 19) completed clinical interviews, self-report questionnaires inquiring about pain history, interference of pain with daily life, and pain catastrophizing, as well as measures of depressive and anxious symptoms. Veterans also underwent single-voxel proton ( 1 H) magnetic resonance spectroscopy (MRS) at 3 T in the anterior cingulate cortex (ACC) using a two-dimensional (2D) J-resolved point spectroscopy sequence. We found no group difference in neurometabolites between veterans with and without chronic pain; however, pain intensity, negative thinking about pain, and description of pain in affective terms were associated with lower GABA/Cre in the ACC. In addition, the Glu/GABA ratio in the ACC was positively associated with anxiety and depressive symptoms in veterans with chronic pain. Reductions in GABA in the ACC may contribute to increased pain intensity and greater pain catastrophizing in veterans with chronic pain. Furthermore, a disturbance in the excitatory-inhibitory balance may contribute to the anxious and depressive symptoms related to chronic pain. Given the pilot nature of the study, these findings must be considered preliminary.